Predicting aggression in late adolescent romantic relationships: A short‐term longitudinal study. (3rd November 2016) - Caiozzo, Christina N.; Houston, Jessica; Grych, John
ABSTRACT: This study sought to prospectively predict aggression in the romantic relationships of 1180 college students from the United States (807 females; 373 males) over the course of two months with a set of intrapersonal risk and protective factors, including personality characteristics that rarely have been examined in this population. After accounting for prior dating aggression, perpetration of verbal aggression was predicted uniquely by aggressive attitudes, emotion regulation, and for females, narcissism. Perpetration of physical aggression was predicted by aggressive attitudes, but only at low levels of emotion regulation, and the interaction of callous‐unemotional traits, emotion regulation, and gender: males with low levels of callous‐unemotional traits perpetrated less physical aggression when they reported greater emotion regulation. These findings are among the first to show that personality traits and emotion regulation prospectively predict partner aggression in late adolescence and suggest mechanisms for continuity in interpersonal aggression from early adolescence to adulthood.